Die Ernennung von Bischöfen in Österreich, Deutschland und der Schweiz - Primetshofer, Bruno (Zeitschrift für katholische Theologie, 1996)
The nomination of bishops in the three countries (Austria, Germany, Switzerland) is partially based on the universal law of the Code (1983), partially, in the single countries, on Concordatarian law. These concordats, according to the Constitution of the single states, are either concluded with the entire state (Deutsches Reichskonkordat, Österreichisches Konkordat) or with parts of it (f. i. Länder, Kantone). According to the concordats in question the cathedral chapter of some dioceses has a right of either free election of the bishop (f. i. Basel and St. Gallen) or of an election out of a list of three candidates presented by the Holy See. If the chapter has the right of free election, this must be followed by papal confirmation. The Holy See insists that the name of the elected bishop is not published before confirmation has been given. In some concordats the Holy See has bound itself to the so-called "praenotificatio officiosa", i. e. before nomination of a residential bishop of a coadjutor bishop takes place, the Holy See confidentially asks the government whether or not there are objections of general political nature against the person of the nominee. According to some concordats bishops, before taking possession of their office, are obliged to swear a loyalty oath in favour of the state. After the Second Vatican Council the question has been risen, if these dispositions still correspond with the now prevailing system of mutual confidence between Church and State.